Attitude Control with Auxiliary Structure Based on Adaptive Dynamic Programming for Reentry Vehicles - Xu Li; Zhongtao Cheng; Bo Wang; Yongji Wang; Lei Liu (Complexity)
This paper presents an attitude control scheme combined with adaptive dynamic programming (ADP) for reentry vehicles with high nonlinearity and disturbances. Firstly, the nonlinear attitude dynamics is divided into inner and outer loops according to the time scale separation and the cascade control principle, and a general sliding mode control method is employed to construct the main controllers for the double loops. Considering the shortage of main controllers in handling nonlinearity and sudden disturbances, an ADP structure is introduced into the outer attitude loop as an auxiliary. And the ADP structure utilizes neural network estimators to minimize the cost function and generate optimal signals through online learning, so as to compensate defect of the main controllers’ adaptability speed and accuracy. Then, the stability is analyzed by the Lyapunov method, and the parameter selection strategy of the ADP structure is derived to guide implementation. In addition, this paper puts forward skills to speed up ADP training. Finally, simulation results show that the control strategy with ADP possesses stronger adaptability and faster response than that without ADP for the nonlinear vehicle system.